Urban Sprawl And Its Consequences On The Sustainability Of Sekondi – Takoradi Metropolitan Area - Atakorah, G.B. (University Of Ghana, 2022)
Cities worldwide are undergoing significant spatial transformation due to continued urban growth and sprawl, with forecasts indicating strong growth in the urban fringe well into the future. Urban sprawl is an ensuing spatial form that has emerged globally due to this spatial transformation of urbanisation and has consequences on the natural and built environment, thereby affecting the sustainability of cities. Sekondi-Takoradi has undergone a series of economic boom and bust years, which has influenced the rate of spatial expansion in the city. The study, therefore, examines urban sprawl in the city and attempts to fill gaps in knowledge by examining the drivers of sprawl and the social and environmental issues affecting its sustainability. A mixed-method approach was used, which sampled 400 households and 120 commercial entities, and conducted 25 interviews and 12 focus group discussions. Among the interesting revelations of the study was the state's role in creating an enabling environment both positive and negative, which the private sector and individuals have taken advantage of and has led to the ongoing unplanned and haphazard development of the city. This has resulted in unequal access to essential services, loss of livelihood and inequality in livelihood options, thereby affecting the social well-being of the inhabitants. Environmentally, the consumption pattern within the city and its ensuing urban heat island effect among others threaten its sustainability, both in the short and long term, with broader implications for the city region. As a result of these threats to the city's sustainability, the study recommends that buffer zones or green belts be implemented beyond which spatial expansion is not permitted to occur, thus shifting towards densification and a more sustainable urban development.
PhD. Geography
Keywords: Urban; Sekondi; Takoradi; Sustainability; Sprawl